2011
DOI: 10.1016/j.postharvbio.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chilling injury in stored nectarines and its detection by time-resolved reflectance spectroscopy

Abstract: Chilling injury in stored nectarines and its detection by time-resolved reflectance spectroscop

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…These results are similar to previous studies [14,19]. Intact apple measurements show a positive correlation (R = 0.5) at 685 nm.…”
Section: Cut Surfacesupporting
confidence: 92%
“…These results are similar to previous studies [14,19]. Intact apple measurements show a positive correlation (R = 0.5) at 685 nm.…”
Section: Cut Surfacesupporting
confidence: 92%
“…The wavelength of 487 nm was found to be the combined absorption peak for carotenoids and chlorophyll in post-harvest ripening of apples (Merzlyak & Solovchenko, 2002). Used to distinguish healthy and cold-injured nectarines (Lurie et al, 2011), absorptions at 656 nm and 774 nm were close to 670 nm and 780 nm for peaches. Hashim et al (2013), used back-scatter imaging at 660 nm to classify between control and cold-injured bananas, depending on changes in the pigment content and texture of the exocarp.…”
Section: Optimal Wavelength Selectionmentioning
confidence: 91%
“…For example, the firmness of peaches stored at in air at 20°C up to 8 days decreased from 45 N to about 0 N (Bonghi, Ramina, Ruperti, Vidrih, & Tonutti, 1999). Lurie et al (2011) reported non-stored nectarine had expressible juice of 45-50% in the first 3 days of shelf life, while this increased to close to 60% for 6 and 7 days of shelf life. For a long time storage, low temperature was widely used to slow the ripening of peaches.…”
Section: Changes Of CI Index and Peach Quality Parametersmentioning
confidence: 98%
See 2 more Smart Citations